Editorial: Optimization of energy autonomy in buildings with renewable energy sources and battery storage - Christodoulides, Paul; Capuder, Tomislav; Georgiou, Giorgos S. (My University, 2024)
The theme of this Frontiers in Energy Research Special Issue (SI) was based on the topic editors’ expertise and previous work (see, for example,Georgiou et al., 2019; Gržanić et al., 2022), and attempted to bring together miscellaneous work addressing keywords such as Building Energy Optimization, nearly Zero Energy Buildings, Electrical Energy Storage, Linear Programming, Artificial Neural Networks, Genetic Algorithm, Convex optimization, Photovoltaics, Demand Side Management, Building Management Systems. All new buildings are currently being built in a way that minimizes primary energy consumption (energy from utility networks) while increasing their percentage of renewable energy sources (RES). The levelized cost of electricity has been rapidly decreasing due to newer, more efficient and cheaper technologies, which to some extent can compete with conventional generation units. Hence, the usage of electrical storage has raised a great interest of both academics and professionals. Furthermore, studies have shown that buildings with electrical storage can reduce electricity bills while increasing selfconsumption of onsite Renewable Energy Generation (REG).
Keywords: building energy optimization; building management systems (BMS); demand side management (DSM); electrical energy storage (EES); nearly zero energy buildings (nZEB)